Effect of sulfonated poly (ether ether ketone) on the sensitivity of polyvinylidene fluoride-based resistive humidity sensors - Shoaib Mallick (14578565) (2020)
We have investigated the effect of sulfonated poly (ether ether ketone) (SPEEK) on the thermal stability, hydrophilicity, and sensitivity of polyvinylidene fluoride (PVDF) films based resistive humidity sensors. The blended film was deposited on the pre-patterned interdigited ITO glass electrode by the spin coating technique. The thermal stability of the PVDF-SPEEK composites investigated by thermogravimetric analysis. The surface morphology of the composite blend films has been studied by field emission scanning electron microscopy and atomic force microscopy analyses. The morphology of the PVDF-SPEEK blend films indicates that the PVDF-SPEEK blend is not uniform at high concentrations of SPEEK (over 10 wt%). The hydrophilicity of the sensing film studied by the contact angle method. As the concentration of SPEEK increases in the blend film, the hydrophilicity of the composite film also increases, which enhances the sensitivity of the sensing film. The impedance response of the PVDF-SPEEK blend film shows that the addition of SPEEK enhances the sensitivity of the sensing film at a lower humidity level. Moreover, the response and recovery times of the PVDF-SPEEK (2.5−5 wt%) are found to be 25 s and 65 s, respectively. Other Information Published in: Materials Today Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.mtcomm.2020.101601